Navigating the rural landscape: understanding the causes of reading difficulties in high school students - Palahang, Joean Balansag (Universitas Merdeka Malang, 2024)
This qualitative research investigates the complex factors contributing to reading difficulties among high school students in a rural area of Mindanao, Philippines. In-depth interviews with students, teachers, and community members provided qualitative insights into the lived experiences and perspectives surrounding reading difficulties. The research identified a multifaceted web of challenges: socioeconomic, environmental, instructional, linguistic, technological, Â health and wellness, school-related, and community factors. The findings highlight the critical need for comprehensive interventions addressing these interconnected challenges. Recommendations include community engagement programs, violence prevention initiatives, professional development for teachers, curriculum enhancement, technology integration, wellness programs, increased school funding, and resource allocation. By addressing these multifaceted issues, educators, policymakers, and community stakeholders can work collaboratively to create a supportive and enriching educational environment for students in rural areas, ultimately enhancing their reading abilities and academic success.